STRATEGIC PRIORITIZATION OF INDIGENOUS MILLET AGRIBUSINESS DEVELOPMENT: AN INTEGRATED SWOT–QSPM APPROACH - Harry Fadly Umamit; L.O. Kakisina; Tienni Simanjorang (Agric, 2026)
Hotong (Setaria italica), a millet crop native to Buru Island in eastern Indonesia, has the potential to diversify local food crops and support smallscale industries. Hotong has agronomic advantages as an alternative food to replace rice and wheat, rich in carbohydrates, protein, and fiber, in addition, this plant is drought-resistant and thrives on marginal land. Hotong has great potential to be processed into various high-value products. However, its development remains constrained by informal seed systems, limited postharvest facilities, weak farmer institutions, and rice-oriented food policies. This study aimed to analyze internal and external strategic factors affecting hotong agribusiness and to determine priority strategies for its development. Field research was conducted in Waenewen Hamlet, Labuang Village, South Buru Regency, Indonesia, involving 60 hotong farming households, village government, representatives of farmers group involved in product processing and marketing. agricultural extension officer., and local processors. Primary data were collected through structured questionnaires, interviews, and focus group discussions, while secondary data were obtained from official and documentary sources, including the Labuang Village monograph, Namrole District profile, statistical publications from BPS, local government documents, food diversification policy reports, and relevant. Data were analyzed using internal factor evaluation (IFE), external factor evaluation (EFE), SWOT matrix, Quantitative Strategic Planning Matrix (QSPM), reliability testing, and sensitivity analysis through ±10% weight adjustment. The results indicate that hotong agribusiness has moderate internal capacity and external opportunity. Certified seed system development emerged as the highest priority strategy, followed by policy alignment with food diversification programs and research–SME collaboration. Sensitivity analysis showed that the top-ranked strategies remained stable under moderate weight adjustment. This study contributes to the development of a strategic planning framework for indigenous crop-based agribusiness systems in small-island contexts by integrating system-based agribusiness analysis, SWOT–QSPM prioritization, and robustness testing.